Aircraft structures for engineering students - Megson, T. H. G. (Thomas Henry Gordon) (Elsevier aerospace engineering series, 2022)
Aircraft Structures for Engineering Students, Seventh Edition, is the leading self-contained aircraft structures course text suitable for one or more semesters. It covers all fundamental subjects, including elasticity, structural analysis, airworthiness and aeroelasticity. Now in its seventh edition, the author has continued to expand the book's coverage of analysis and design of composite materials for use in aircraft and has added more real-world and design-based examples, along with new end-of-chapter problems of varying complexity.